A freestanding ferroelectric thin film-based soft strain sensor - Jianping Guo; Zelong Wang; Guo Tian; Deyang Chen; Xingsen Gao; Xiaoyuan Zhou; Jiangyu Li; Ji-Yan Dai (Journal of Materiomics)
Flexoelectric and photo-flexoelectricity are scientifically intriguing and hold considerable potential for various applications such as soft strain sensing, photovoltaics, energy harvesting, etc. Among flexoelectric materials, freestanding ferroelectric thin films are believed to have huge flexoelectricity and tunability due to their excellent lattice regulatory freedom and sustainability to larger strain gradients. In this work, we demonstrated a freestanding BiFeO3(BFO) thin film-based soft strain sensor and explored their flexoelectric coefficient and flexoelectric photovoltaic effect under different strain gradients. Under different bending scales, the photocurrent of the thin film exhibits a step-like variation, indicating that the sensor can measure strain gradient with high sensitivity. These results show the potential application of freestanding ferroelectric films in flexible devices.